2004
DOI: 10.1002/cyto.a.20031
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of presynaptic and postsynaptic markers by size‐based gating analysis of synaptosome preparations from rat and human cortex

Abstract: Background: Synapse regions in the brain are difficult to isolate and study; resealed nerve terminals (synaptosomes) are a widely used in vitro system for the study of neurotransmission, but nonsynaptosomal elements in the homogenate complicate data interpretation. With the goal of quantitative analysis of pathways leading to synapse loss in neurodegenerative disease, we have developed a method that allows focus on the intact synaptosomes within a crude synaptosomal preparation by gating the largest particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 29 publications
2
60
0
Order By: Relevance
“…The proportion of gated particles containing PSD95 reached nearly 90% and did not differ between the genotypes. This is well above the level of purity achieved by a comparative study by Gylys et al where synaptosomes were analyzed with and without size exclusion gating (Gylys et al, 2004b). The proportion of particles that contained both the presynaptic marker synaptophysin and the postsynaptic maker PSD95 was also significantly enriched by gating (p < 0.001, n = 6) and reached 70%.…”
Section: Isolation and Characterization Of Synaptoneurosomes From Adumentioning
confidence: 83%
See 1 more Smart Citation
“…The proportion of gated particles containing PSD95 reached nearly 90% and did not differ between the genotypes. This is well above the level of purity achieved by a comparative study by Gylys et al where synaptosomes were analyzed with and without size exclusion gating (Gylys et al, 2004b). The proportion of particles that contained both the presynaptic marker synaptophysin and the postsynaptic maker PSD95 was also significantly enriched by gating (p < 0.001, n = 6) and reached 70%.…”
Section: Isolation and Characterization Of Synaptoneurosomes From Adumentioning
confidence: 83%
“…Forward scatter (FSC), side scatter (SSC) and fluorescence intensity (measured as fluorescent area, A) were analyzed with logarithmic amplification. The gating was set to only include particles with a relatively high SSC and FSC into the analysis as described previously for synaptosomes (Gylys et al, 2004b). To ensure that this gating increases the proportion of synaptoneurosomes in the analyzed fraction, immunostaining for synaptic proteins was performed.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…34e36 These animals are homozygous for the following three gene constructs: i) human APP 695 with the K670N/M671L mutation (rat synapsin-1 promoter); ii) human APP minigene with the K670N/M671L and V717F mutations (platelet-derived growth factor b promoter); and iii) human presenilin-1 with the M146V mutation (rat synapsin-1 promoter). This model exhibits age-associated Ab pathology, with sparse hippocampal plaques seen by 9 ajp.amjpathol.org -The American Journal of Pathology Flow Cytometric Analysis of Synaptosome-Enriched P-2 Fraction P-2 fractions (synaptosome-enriched fractions) were prepared from cryopreserved brain tissue as described previously, 37 cryopreserved in 0.32 mol/L buffered sucrose solution and stored at À80 C as aliquots. On the day of the experiment, aliquots were quickly defrosted at 37 C, and P-2 pellets were collected by centrifugation.…”
Section: Animalsmentioning
confidence: 99%
“…Synaptosomes are primarily presynaptic and contain mitochondria, endosomes, and exocytotic structures 40 ; some postsynaptic elements are also present, with approximately 36% of particles positive for postsynaptic density protein 95. 37 Comparison of synaptosomal proteins with proteins in undisturbed brain slices has shown that synaptic bouton protein composition is maintained in synaptosomes. 41 Demographic and neuropathologic data for the normal control, HPC, and AD cases are shown in Table 1.…”
Section: Total In Situ Synaptic Ab Is Associated With Plaque Level Inmentioning
confidence: 99%
“…There are several variations and combinations of filtration, 5,[14][15][20][21][22][23] centrifugation, [24][25][26][27] and gradient methods [26][27][28][29] that have been used to prepare SNs and each has its own advantages and disadvantages. Filtration and centrifugation methods can cause mechanical damage to the SNs.…”
Section: Preparation Of Homogenate and Sns 1-4 4 Representative Resumentioning
confidence: 99%